Contingency as an entrepreneurial resource: How private obsession fulfills public need - Harmeling, Susan (Journal of Business Venturing, 2011)
Borrowing from Rorty (1989:37), this article portrays the entrepreneurial process as a mechanism through which “private obsession” fulfills “public need.” It begins with an argument that a deeper understanding of contingency can enhance management scholarship in general and entrepreneurship in particular. It continues with an examination of contingency and entrepreneurial opportunity and then uses six narratives to show how both personal and historical contingencies become resources in the entrepreneurial process. A depiction of possible alternative responses (counterfactuals) for each narrative illustrates how entrepreneurs tend to take a resourceful, rather than an adaptive or a heroic stance toward contingency. A discussion of American Pragmatism provides theoretical support for contingency's role in the entrepreneurial process. The paper concludes with a literature review and a look at how this view of entrepreneurial contingency illuminates the temporal context in management scholarship, among other implications for both research and practice.